First-principles investigations on ferromagnetic behaviour of Be1−xVxZ (Z = S, Se and Te) (x = 0.25). (December 2015) - Doumi, B.; Mokaddem, A.; Sayede, A.; Dahmane, F.; Mogulkoc, Y.; Tadjer, A.
Abstract: The structural, electronic and magnetic properties of beryllium chalcogenides such as BeS, BeSe and BeTe doped with magnetic vanadium (V) impurity as ternary Be1− x V x Z (Z = S, Se and Te) compounds in zinc blende phase have been performed at concentration x = 0.25, by employing first-principles calculations of full-potential linearized augmented plane-wave method within the framework of density functional theory. The electronic structures of Be0.75 V0.25 Z (Z = S, Se and Te) compounds revealed a half-metallic ferromagnetic character with 100% spin polarized that emerges this behavior results from the band gap of minority spin and metallic nature of majority spin due to a strong hybridization between 3 d (V) and p (S, Se and Te) states dominating at Fermi level. According to the results of magnetic properties calculations, the total magnetic moments of Be0.75 V0.25 Z (Z = S, Se and Te) are integers Bohr magneton of 3 μB that confirms the half-metallic behavior of these compounds. Therefore, the Be0.75 V0.25 Z (Z = S, Se and Te) compounds seem to be potential candidates to explore half-metallic ferromagnetism property for near future applications in spintronics. Graphical abstract: The prototype supercell structures of 8 atoms for (a) Be0.75 V0.25 S, (b) Be0.75 V0.25 Se and (c) Be0.75 V0.25 Te. Highlights: The half-metallic ferromagnetism is predicted in Be0.75 V0.25 Z (Z = S, Se and Te). The 3d - t 2g (V) partially filled states stabilize the ferromagnetic state. The Be0.75 V0.25 Z compounds seem to be potential candidates for future applications in spintronics.